Association between atherosclerotic aortic plaques and left ventricular hypertrophy in patients with cerebrovascular events - Hueb, João Carlos [UNESP]; Zanati, S. G.; Okoshi, Katashi [UNESP]; Raffin, C. N.; Silveira, LVD; Matsubara, Beatriz Bojikian [UNESP] (Lippincott Williams & Wilkins, 2006)
Background and Purpose - the purpose of this research was to evaluate whether an association exists between the presence of atherosclerotic plaque in the thoracic aorta and left ventricular hypertrophy (LVH) in patients with a cerebrovascular event.Methods - We included 116 consecutive patients ( 79 men; mean age, 62 +/- 12.4 years) with previous history of stroke or transient ischemic attack in a cross-sectional study. Transthoracic echocardiogram was performed to diagnose LVH and transesophageal echocardiogram for the detection of atheromas of the thoracic aorta. Continuous variables were analyzed by Student t or Mann-Whitney tests and categorized variables by Goodman test. From the significant association of LVH and age with atheromatous disease of the aorta, an adjustment to the multivariate logistic model was made using high blood pressure history or age as covariates. All of the statistical tests were carried out at a level of 5% significance.Results - Almost half of the patients (43.1%) presented atherosclerotic lesions in the aorta. LVH was present in 90.0% of patients with plaque and in only 30.3% of patients without plaque. Using high blood pressure as a covariate, the risk of patients with LVH presenting atherosclerotic plaque in the aorta was 18.23-fold greater than the risk for patients without LVH (95% CI, 5.68 to 58.54; P < 0.0001). Adding age into the model, the risk increased to 26.36 ( 95% CI, 7.14 to 97.30; P < 0.0001).Conclusions - LVH detected by conventional echocardiogram is associated with high risk of atherosclerotic plaque in the aorta and would be used as a criterion for indication of transesophageal echocardiography in patients with previous stroke or transient ischemic attack LVH.
Keywords: echocardiography; left ventricular hypertrophy; stroke; transient ischemic attack